Comparison between subarachnoid morphine and femoral nerve block for analgesia after knee ligament reconstruction: a randomized clinical trial - Fiorentin,Joana Zulian (2020)
Abstract Background and objectives There are no consensus of the ideal technique to provide analgesia in knee ligament reconstructions. The aim of this study was to compare the intensity of postoperative pain in these patients under different modalities of analgesia. Method Randomized and controlled clinical trial of patients undergoing reconstruction of the Anterior Cruciate Ligament (ACL) with flexor tendons between December 2013 and 2014. All patients underwent spinal anesthesia and rescue analgesia with tramadol. The groups C, M, R0,375 and R0,25 was compared with only the previously described technique, subarachnoid morphine (100░µg), or Femoral Nerve Block (BNF) with 25░mL of 0.375% ropivacaine and 0.25%, respectively. Pain intensity at 6, 12 and 24░hours, age, sex, rescue analgesia, adverse reactions and satisfaction were evaluated. Results Among the 83 eligible patients, a predominance of males (85.7%) was observed, between 28 and 31 years. The group C requested more opioid (27.3%) than the other groups, without significance when compared. There were no significant differences in pain intensity at 6, 12 and 24░hours. There was a higher incidence of urinary retention in the M group (23.8%) than in the R0,375 (0%) and prolonged quadriceps motor block in the R0,375 group (30%) than in the M and C groups (0%), with statistical significance (p░<░0.05). Conclusion There was no difference in the intensity of postoperative pain in patients submitted to ACL reconstruction with flexor tendons under the analgesic modalities evaluated, despite the predominance of urinary retention in the M group and motor block in the R0,375 group.